Development of Tourism Villages Through Digitalization and Micro/Small/Medium Enterprises (MSMEs) Potential in Kepyar Village, Wonogiri - Ramelan, Agus; Aulia Putra, Mufti Reza; Pratama, Muhammad Iksan Bima Aria; Hidayat, Muhammad Nur; Ekasuci, Zahra Fadilla; Nugroho, Alka Adi; Anam, Muhammad Choirul; Parawansa, Monalisa Indah; Putra, Reyza Fachrezy; Restanti, Arlinda Dwi; Solikhah, Yuliana Ayunta; Fayza, Ayu Nur (REKA ELKOMIKA: Jurnal Pengabdian kepada Masyarakat, 2024)
Kepyar Village has great potential to be developed as a tourist village through empowering tourism potential and MSMEs. The service activities carried out aim to increase the knowledge and skills of the Kepyar Village community regarding the implementation of digitalization in developing tourist villages. Service activities consist of developing digitalization of MSMEs and village tourism potential through websites. Digitalization of MSMEs is carried out through digital marketing outreach, assistance in creating a Google My Business account, as well as digital marketing assistance through the TikTok Shop application. The development of a tourist village website is carried out by observing natural potential and MSMEs, creating a website, and socializing the results of the website. Follow-up efforts that can be taken include handing over the website to the village and providing assistance to manage it independently, providing assistance to the community to develop and manage tourism and MSMEs digitally, as well as evaluating the performance and success of the digitalization program that has been attempted to be carried out. development of services and marketing methods that suit people's preferences.